PENGARUH VARIETAS, PEROMPESAN DAUN, DAN PENYEMPROTAN FUNGISIDA TERHADAP INTENSITAS PENYAKIT KARAT (Puccinia horiana P. Henn.) PADA TANAMAN KRISAN (Dendranthema grandiflora Tzvelev) - E Silvia Yusuf; - Suhardi (Agric, 2013)
Puccinia horiana P. Henn. is the pathogen which caused of white rust on chrysanthemum. It is the most serious disease on chrysanthemum. Study on the effect of varieties, defoliation, and fungicide application against rust diseases (Puccinia horiana) was carried out under plastic house of Institute of Ornamental Crop Research at Segunung (alt. 1100 m asl) from July - November 2008, using Split-split plot design in three (3) replications. The main plot was chrysanthemum cultivar (cv. ILK.6B1, cv. Giant and cv. Cat eye); sub-plot was defoliation and sub-sub plot was application of fungicide. The results indicated that a) cv. Cat Eye, cv. ILK.6B1 (aster/Reagent) and cv. Giant were resistant, moderately resistant, and susceptible against rust caused by Puccinia horiana respectively; b) defoliation was able to reduce disease intensity of rust as much as 44 percent at the beginning, but only 3-21 percent on the further observations; c) fungicide application was able to reduce disease intensity as much as 20-49 percent; d) defoliation and fungicide application did not significantly influence the number of flowers, plant height and flower diameter.